Change in cognitive performance during seven-year follow-up in midlife is associated with sex, age, and education : The Cardiovascular Risk in Young Finns Study - Heiskanen, Marja A.; Nevalainen, Jaakko; Pahkala, Katja; Juonala, Markus; Hutri, Nina; Kähönen, Mika; Jokinen, Eero; Laitinen, Tomi P.; Tossavainen, Päivi; Taittonen, Leena; Viikari, Jorma S. A.; Raitakari, Olli T.; et al. (Germany, 2025)
Objective: Sex, age, and education are associated with the level of cognitive performance. We investigated whether these factors modulate the change in cognitive performance in midlife by leveraging the longitudinal data from the Cardiovascular Risk in Young Finns Study (YFS).
Methods: Participants of the YFS cohort performed a computer-based Cambridge Neuropsychological Test Automated Battery (CANTAB) in 2011 and 2018 (n = 1671, age 41-56 years in 2018). Overall cognitive performance and domains representing learning and memory, working memory, reaction time, and information processing were extracted by common principal component analysis from the longitudinal cognitive data. Linear models adjusted for baseline cognitive performance were used to study the association of sex, age, and education with changes in overall cognitive performance and in the cognitive domains.
Results: Cognitive performance decreased in all domains (overall cognition -0.56 SD, p < 0.001; working memory -0.81 SD, p < 0.001; learning and memory -0.70 SD, p < 0.001; reaction time -0.06 SD, p = 0.019; information processing -0.03 SD, p = 0.016). The decrease in working memory and information processing was greater in females compared to males. Cognitive performance decreased more in older participants in all domains. Education alleviated the decrease in cognitive performance in all domains except reaction time. The beneficial effect of education was greater for males.
Conclusions: This study describes the natural course of aging-related changes in cognitive performance in midlife, the critical time window for early prevention of clinical cognitive decline. These findings provide a reference for studies focusing on determinants of pathological cognitive decline deviating from normal changes in cognitive performance.